circASAP1 induces renal clear cell carcinoma ferroptosis by binding to HNRNPC and thereby regulating GPX4 - Yunfei Wang; Taowei Yang; Qihao Li; Zhousan Zheng; Lican Liao; Junjie Cen; Wei Chen; Junhang Luo; Yi Xu; Mi Zhou; Jiaxing Zhang (Molecular Cancer)
Abstract Background Clear cell renal cell carcinoma (ccRCC) represents the most prevalent subtype, accounting for nearly 80% of all RCC cases. Recent research has shown that high expression of circular non-coding RNA (circRNA) is associated with poor prognosis in patients with renal clear cell carcinoma (ccRCC), however, the underlying mechanism remains unclear. Methods After analysing self-sequenced renal cancer and paracancer circRNA sequencing data and comparing it with the GEO public database, we discovered that circASAP1 expression was significantly up-regulated in renal cancers. We also tested circASAP1 levels in 102 renal cancer patients and found that high expression of circASAP1 was associated with poor prognosis and metastasis. The interaction between circASAP1, HNRNPC and their downstream target genes was confirmed through experiments such as RNA pull-down, RIP and fluorescence in situ hybridisation. A series of in vitro and in vivo functional experiments were performed to verify the effects of circASAP1 on RCC proliferation and metastasis. Results Circular RNA sequencing analysis revealed that circASAP1 expression was markedly elevated in ccRCC, with a significant association observed between elevated circASAP1 expression and poor prognosis and metastasis. Actinomycin D, RNase R, as well as fluorescence in situ hybridization (FISH) analyses revealed the ring structure and cytoplasmic localization of circASAP1. High circASAP1 expression was associated with ccRCC cell proliferative viability, invasion, and metastasis in CCK-8, transwell, plate cloning, and EdU experiments. Interaction of circASAP1 with HNRNPC and their downstream target genes was confirmed by RNA pull-down, RNA immunoprecipitation, FISH, silver staining, and mass spectrometry. Experiments using truncated isoforms demonstrated that amino acids 16–87 of HNRNPC bound circASAP1. Proteins altered by circASAP1 were enriched in the ferroptosis pathway on the Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis. Conclusions The relationship between circRNA and the ASAP1/HNRNPC/GPX4 axis was demonstrated by experimental data, which was further confirmed by rescue experiments. circASAP1 influenced tumor growth and ferroptosis in animal experiments and predicted the prognosis of patients with ccRCC. The circASAP1/HNRNPC/GPX4 axis provides novel directions and potential targets for RCC treatment.